Radiogenic Sr and Stable C and O Isotopes Across Precambrian‐Cambrian Transition in Marine Carbonatic Phosphorites of Malyi Karatau (Kazakhstan)—Implications for Paleo‐environmental Change. (3rd January 2019) - Stammeier, J. A.; Hippler, D.; Nebel, O.; Leis, A.; Grengg, C.; Mittermayr, F.; Kasemann, S. A.; Dietzel, M.
Abstract: The Precambrian‐Cambrian (PЄ‐Є) transition is a unique period in Earth's history known for the "Cambrian Explosion." Here we present a continuous radiogenic and stable isotope ( 87 Sr/ 86 Sr, δ 13 CVPDB, carb, and δ 18 OVPDB, carb ) and elemental (including rare earth elements) record across the PЄ‐Є transition, preserved in phosphatic and carbonate shallow‐water deposits from two sections (Koksu and Kyrshabakty) in Kazakhstan. Microstructure, trace, and rare earth elements concentrations reflect near‐primary preservation. δ 13 CVPDB, carb data (−12.1‰ to 3.3‰) record formation conditions at a time of severe geodynamic changes. Negative δ 13 CVPDB, carb at the PЄ‐Є boundary resemble the Basal Cambrian Carbon Anomaly. Average δ 18 OVPDB, carb values of −11.7 ± 3.8‰ are suggested to represent near‐primary signals and can be explained by isotopically lighter past sea water and elevated temperature during precipitation compared to present‐day conditions. Initial 87 Sr/ 86 Sr of the carbonate and phosphate fraction are in the range of 0.7086–0.7112 at the Koksu section and 0.7082–0.7136 at the Kyrshabakty section. This is in general agreement with the seawater 87 Sr/ 86 Sr evolution during the Early Cambrian. In this study, we present a refined 87 Sr/ 86 Sr seawater evolution, highlighting an extreme positive Sr isotope excursion at the PЄ‐Є transition, which is suggested to be indicative for enhanced continental weathering and an increase in nutrient runoff into shallow ocean waters. This extreme geodynamic event may have served as a driving force for enhanced biologic activity in the lead up to the Cambrian Explosion, where phosphatic shallow‐water deposits from Kazakhstan constitute a valuable paleo‐environmental archive. Key Points: We present the first continuous 87 Sr/ 86 Sr record from Kazakhstan across the Pc‐C transition A refined 87 Sr/ 86 Sr seawater evolution is presented with distinct positive excursion at the Pc‐C transition corresponding to a negative δ 13 C anomaly (BACE) Enhanced continental weathering was a driving force for the Cambrian Explosion